Shelf-life of green asparagus using cassava and chitosan blend coating - Aroucha, Edna; Anastasiadi, Maria; Collings, Emma R.; Araujo, Nicolas; Terry, Leon A. (SciELO - Scientific Electronic Library Online, 2024)
Polysaccharide coating is a biodegradable alternative to conventional packings used for delaying senescence in vegetables. This work investigated the properties of cassava and chitosan biopolymeric film and its use as edible coatings to preserve the shelf-life (7 °C and 70% relative humidity (RH)) of green asparagus, with previous cold storage (1 °C and 90% RH) for 7 days. Based on a previous assessment of the films obtained from a) cassava (2.5%), b) chitosan (0.5%), and c) a blend of cassava-chitosan (Cassava+) (2.5 + 0.5%), it could be verified that cassava-chitosan blend films showed improved barrier property (water vapor transmission rate (WVTR) of 38.06 g/(m2.h)) and mechanical properties, with tensile strength of 0.021 MPa, elongation at break of 1.93% and Young’s module of 0.011 MPa. Cassava+ based coating resulted in a lower weight loss and colour L* parameter and minimized textural changes in basal-section of commercial green asparagus spears during a shelf-life of seven days (7 °C and 70% RH), with previous cold storage. All coated spears maintained overall higher carbohydrate levels than the control, except to sucrose which gradually decreased in basal sections and increased in the apical sections of asparagus spears, irrespective of treatment. Edible coating did not affect asparagine concentrations which steadily increased throughout the shelf-life of the spears. The blend (Cassava+) kept for a longer the green asparagus quality. However, spears under a shelf-life of seven days (7 °C and 70% RH), with previous cold storage under 1 °C and 90% RH conditions, developed tip-rot physiological disorder.
Keywords: Asparagus officinalis; Modified atmosphere; Biopolymer; Mechanical properties; Blend; Starch